Les preuves de la filiation - Pineau, Jean (Les Cahiers de droit, 1981)
In adopting Bill 89, the National Assembly, while retaining most of the wording of the rules proposed by the Civil Code Revision Office, has changed their order and arrangement. This may entail substantive alterations. The first part of this paper shows that, on a first reading at least, the new provisions display some consistency. The terms « legitimacy » and « legitimate » are no longer used; children are treated alike, especially as regards the manner of proof whether they be born from wedlock or not. Maternity and paternity may now be proved by similar means. The various modes of proof are now hierarchically listed : first come acts of birth, followed in sequence of subsidiarity by possession of status, presumption as to the husband's paternity, and recognition. The traditional presumption is therefore significantly downgraded. In litigated cases, the action to disavow paternity is now open not only to the mother's husband, but also to the mother herself. Status may be challenged and a different one may be sought whenever the act of birth and possession of status are not congruent. Biological truth is given precedence over the protection of legitimacy In the second part of the paper, however, some inconsistencies in the new provisions are brought out. They relate mainly to two issues. The new provisions purportedly make no distinction between the proof of maternity and that of paternity. Yet, while maternity may be proved directly, the proof of paternity must remain somewhat uncertain, hence the use of presumptions. Most useful among these is the presumption as to the husband's paternity : yet the new provisions confine it to a very subsidiary role. According to the new scheme of rules, it is questionable whether anyone other than the mother's husband may rely on them to disavow paternity when his name appears on the act of birth. The new provisions also purport to abandon the concept of legitimacy. This, it might be claimed, entails the abandonment of marriage itself. Yet, not only does the new Code preserve marriage, but it also denies recognition to the union de fait. Neither have the presumption as to the husband's paternity, or the disavowal of children, been eradicated from the new provisions. The paper concludes by foreseeing many difficulties in the application of the new rules as to the proof of paternal filiation.